Systemic panniculitis‐like T‐cell lymphoma with involvement of mesenteric fat and subcutis. (9th December 2014) - Lester, Laura; Ewalt, Mark; Warnke, Roger; Kim, Jinah
<x xml:space="preserve">Abstract</x> Subcutaneous panniculitis‐like T‐cell lymphoma (SPTCL) is an uncommon non‐Hodgkins primary cutaneous lymphoma that typically presents as subcutaneous nodules on the extremities or trunk. Here, we report an unusual case of systemic panniculitic T‐cell lymphoma with predominantly mesenteric extra‐cutaneous involvement and an aggressive clinical course with histopathologic and immunophenotypic features that mimic SPTCL. This case serves to expand the body of literature regarding systemic SPTCL‐like disorders with prominent extra‐cutaneous involvement.